Livestock's long shadow : environmental issues and options - Steinfeld, Henning; Gerber, Pierre; Wassenaar, T. D.; Castel, Vincent; Rosales M., Mauricio; Haan, Cees de.; Food and Agriculture Organization of the United Nations; Livestock, Environment and Development (Firm) (Rome : Food and Agriculture Organization of the United Nations, 2006)
This report aims to assess the full impact of the livestock sector o n environmental problems, along with potential technical and policy app roaches to mitigation. The assessment takes into account direct impacts , along with the impacts of feed crop agriculture required for livestoc k production. The livestock sector emerges as one of the top two or thr ee most significant contributors to the most serious environmental prob lems, at every scale from local to global. The findings of this report suggest that it should be a major policy focus when dealing with proble ms of land degradation, climate change and air pollution, water shortag e and water pollution, and loss of biodiversity. Livestock's contributi on to environmental problems is on a massive scale and its potential co ntribution to their solution is equally large. The impact is so signifi cant that it needs to be addressed with urgency. Major reductions in im pact could be achieved at reasonable cost.
"The assessment builds on the work of the Livestock, Environment and Development (LEAD) Initiative"--Pref.
"TC/M/A0701E/1/11.06/5000"--P. [4] of cover.
Includes bibliographical references.
Keywords: Livestock -- Ecology; Animal industry -- Environmental aspects; Biodiversity; Environmental degradation